2014
DOI: 10.1261/rna.048959.114
|View full text |Cite
|
Sign up to set email alerts
|

Refined secondary-structure models of the core of yeast and human telomerase RNAs directed by SHAPE

Abstract: Telomerase catalyzes the addition of nucleotides to the ends of chromosomes to complete genomic DNA replication in eukaryotes and is implicated in multiple diseases, including most cancers. The core enzyme is composed of a reverse transcriptase and an RNA subunit, which provides the template for DNA synthesis. Despite extensive divergence at the sequence level, telomerase RNAs share several structural features within the catalytic core, suggesting a conserved enzyme mechanism. We have investigated the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…A similar alternative structure for free human TER was also proposed based on sequence analysis [19], and this structure is consistent with smFRETdata [51]. SHAPE analysis supports pseudoknot folding for S. cerevisiae and human TER t/PK [52]. A recent study using in vivo chemical probing (DMS) also apparently showed that the pseudoknot does form in the protein-free human TER, but the template is sequestered and becomes more exposed on TERT binding [53].…”
Section: Ter Structure and Assembly With Tertsupporting
confidence: 63%
“…A similar alternative structure for free human TER was also proposed based on sequence analysis [19], and this structure is consistent with smFRETdata [51]. SHAPE analysis supports pseudoknot folding for S. cerevisiae and human TER t/PK [52]. A recent study using in vivo chemical probing (DMS) also apparently showed that the pseudoknot does form in the protein-free human TER, but the template is sequestered and becomes more exposed on TERT binding [53].…”
Section: Ter Structure and Assembly With Tertsupporting
confidence: 63%
“…The pseudoknot of the conserved catalytic center of hTR comprises over half of the core domain, and contains base triples at the junction between the paired stems ( Fig. 2A and B) (14,35,36). In budding yeast, analogous base triples have been shown to contribute directly to catalysis through an unknown mechanism and are located within cross-linking distance from the template (13).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the circular permutation at nucleotide 173 leads to robust activity (Fig. 2C, lane 18), even though it is located within newly proposed base triples (35).…”
Section: Resultsmentioning
confidence: 99%
“…the secondary structure model of the entire 181-nt Est1 arm of TLC1 (nucleotides 514-694) in vitro. We used selective 2 ′ -hydroxyl acylation analyzed by primer extension (SHAPE) to chemically interrogate physical flexibility at each position of purified in vitro-transcribed RNA (Wilkinson et al 2006) using methods described for the catalytic core of yeast and human telomerase RNAs (Niederer and Zappulla 2015). Nucleotides predicted to comprise apical loops of the two hairpins and the 5-nt bulge in the secondary structure model were highly reactive, showing that they are flexible and suggesting that they are indeed unpaired ( …”
Section: Shape Analysis Of the Est1 Arm Of Tlc1 Rnamentioning
confidence: 99%
“…2A). SHAPE was performed as recently described (Niederer and Zappulla 2015). Of note, 2 pmol of purified TLC1 Est1-arm RNA suspended in 8 μL 0.5× TE was denatured at 95°C for 2 min, then cooled on ice for 3 min.…”
Section: Cdc13-est2 Fusion-protein Experimentsmentioning
confidence: 99%